Construction Meaning of Bude Trieng Toys (Rifles) in Physics: Traditional Toys - Maknuni, Jauharil; Sabaruddin (Proceeding International Conference on Science and Engineering, 2020)
Physics is closely related to human life, without realizing we have implemented it in daily life such as when working, walking and other activities, not only adults but also children. When talking about physics we definitely think that physics was born from the west. Before the development of the west in the 9th Century AD, Physics was used in society, especially the people of Aceh. It is undeniable that technology has developed more rapidly now. Technology was created to facilitate human affairs. There are innumerable kinds of technologies. One example of a very popular technology is gadgets. Every person uses gadgets with modern technology such as smart phones, Children have now become active consumers in which many electronic products and gadgets make children the target market for their toys. Before the era of sophisticated technology one of the toys chosen by most children was the Bude Trieng (shotgun). Bude Trieng is marked by playing activities both by himself and other peer groups. i is one toy that quite safe and most popular with children. This type of toy is made from bamboo using paper bullets or boh ram. The method of application is insert boh Ram's bullet in the base of the bude trieng, the ram bullet fills the entire circle of the trieng bude hole, the air inside the Bude trieng will automatically be restrained and cannot come out. The air that is held in the middle of the trieng bude will produce pressure when one of the bullets is pushed and will make a sound from the bude trieng. The purpose of this research is to study the construction of the meaning of bude trieng culture in physics. The research method used was a descriptive qualitative research to describe the relationship between the bude trieng and physics.